Evaluation of the library management program as a learning resources with Discrepancy Model - A. Ardiansah; Diemas Arya Komara; Lien Halimah (Curricula: Journal of Curriculum Development, 2022)
Monitoring and evaluation activities in this study focused on evaluating the school library management program as a learning resource at SMA Sumatra 40 Bandung using the discrepancy model. The research method used is a qualitative approach and a literature review that is processed descriptively. Based on the results of the study, it is known that several aspects evaluated at the Sumatra 40 Bandung High School Library are related to the implementation of the library management program, which has reached high school library standards following Peraturan Kepala Perpustakaan Nasional Republik Indonesia Nomor 12 Tahun 2017 tentang Standar Nasional Perpustakaan Sekolah Menengah Atas/Madrasah Aliyah. However, the aspect of library human resources has not met the standards applied. Recommendations that should be considered by the SMA Sumatra 40 Bandung Library are adding library staff and expanding the library space, and using information and communication technology so that the library management program as a learning resource can be maximized.